Development of expert system for ISO 9606-1 : qualification testing of welders - fusion welding - Tan, Ee Rong. (2013)
Welding has to be performed with quality and according to standard to ensure the structural integrity of the component. The ISO 9606:1-2012 Qualification testing of welders - Fusion welding, regulates the qualification of welders and ensures that weld produced by these personnel is of quality that is recognised globally. An application has been developed to help in the qualification testing in an organized manner, incorporating the requirements of test standard and designed according to usability guidelines. This report reviews the various welding processes as specified in the standard and gives an account of the development process and features of the application.